Exploring the Psychological Stress, Anxiety Factors, and Coping Mechanisms of Critical Care Unit Nurses During the COVID-19 Outbreak in Saudi Arabia - Ali, Shaimaa Ahmed Awad; Diab, Samar Salah Eldin Mohamed; Elmahallawy, Ehab Kotb (Frontiers in Public Health, 2021)
Background: The spread of coronavirus disease 2019 (COVID-19) throughout the world leads to a series of modifications of several National Health Service organizations, with a potential series of psychological consequences among nurses. Methods: This study was undertaken to assess the psychological stress, anxiety factors, and coping mechanisms of critical care unit nurses during the COVID-19 outbreak. A cross-sectional research design was employed, and the convenience sample consisted of 469 nurses working at several hospitals in Saudi Arabia during the period from July to September 2020. This study used the Generalized Anxiety Disorder, Coping Mechanism, and Nursing Stress scale. Results: Interestingly, more than one-third and one-quarter of the studied nurses had severe and moderate anxiety levels, respectively. In addition, the most anxiety-causing factors included providing care for their infected colleagues and worrying about infecting their families. More than one-quarter and slightly less than half of the studied nurses had high and moderate stress levels, respectively. Furthermore, more than half of the participants had low coping mechanisms and one-quarter had moderate coping mechanisms. In addition, there was a strong positive correlation between anxiety and stress levels, and there was a strong negative correlation between coping mechanisms and stress and anxiety levels. Conclusions: Collectively, this study explored the psychological stress, anxiety factors, and coping mechanisms among critical care unit nurses during the COVID-19 outbreak in Saudi Arabia. Continuous educational programs for nurses on using coping mechanisms should be developed in combination with teaching preventive measures for defining a psychological intervention plan within a mandatory occupational health surveillance program. This study recommends that constructive planning and necessary provision of supportive measures by the legal authorities and policymakers protect nurses and minimize their psychological stress to fulfill high-quality nursing care.